Why Adjudicate? : Enforcing Trade Rules in the WTO - Davis, Christina L., 1971- (Book collections on Project MUSE., 2012)
The World Trade Organization (WTO) oversees the negotiation and enforcement of formal rules governing international trade. Why do countries choose to adjudicate their trade disputes in the WTO rather than settling their differences on their own? In Why Adjudicate?, Christina Davis investigates the domestic politics behind the filing of WTO complaints and reveals why formal dispute settlement creates better outcomes for governments and their citizens. Davis demonstrates that industry lobbying, legislative demands, and international politics influence which countries and cases appear before the WTO.